PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI PADA PRODUK UMKM: STUDI KASUS HARUMANIS BANG TOYIB DESA KESAMBI - Ardani, Krisna Yusuf; Purnomo, Nanto (Media Mahardhika, 2025)
This study aims to examine the influence of price and product quality on consumers' purchase intention of Harumanis Bang Toyib products in Kesambi Village. In the midst of increasingly intense competition among small businesses, understanding the key factors that drive consumer purchasing decisions is essentialA quantitative method was applied through a survey approach, where data were obtained using questionnaires and analyzed through multiple linear regression techniques. The findings reveal that price and product quality each exert a positive and significant impact on consumer purchase intention, both separately and when considered together. These findings highlight the importance of price perception and consistent product quality in shaping consumer interest. Therefore, business owners are encouraged to implement competitive pricing strategies and maintain high product standards to enhance consumer trust and market.